Muslim rulers and rebels everyday politics and armed separatism in the southern Philippines - McKenna, Thomas M. 1952- (Comparative studies on Muslim societies, 1998)
An account of the Muslim separatist rebellion in the Philippines. It examines Muslim separatism against a background of more than four hundred years of political relations among indigenous Muslim rulers, their subjects, and external powers seeking the subjugation of Philippine Muslims.